Icon and Network: Didactic Diagnosis of Communication Proposals - Viñas Limonchi, Manuel; Oliva Cantín, Héctor (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This study places artistic and design praxis within the academic field, analysing —in a diagnostic way— the student's creative competencies in communication skills through the argument involved in the creation of a post conceived as an introductory mechanism for an advertising project. The methodology establishes a review of teaching innovation procedures applied to a practical activity belonging to a Communication´s degrees subject. The expected results suggest the didactic relevance of increasing certain student´s creative capacities through different design interventions applied in the communicative environment related to social networks.